Splicing of the U6 RNA precursor is impaired in fission yeast pre-mRNA splicing mutants. - Potashkin, J (1989)
U6 RNA is a member of a class of small abundant stable nuclear RNAs that are essential for splicing. In all species examined so far, the U6 RNA is a RNA polymerase III transcript. The U6 gene of the fission yeast Schizosaccharomyces pombe is unusual in that it is interrupted by an intron whose structure is similar to those found in pre-mRNAs. As part of our previous analysis of three S. pombe temperature sensitive pre-mRNA splicing mutants we examined their spliceosomal snRNA content. In contrast to the other snRNAs, the amount of U6 RNA is reduced at the restrictive temperature in all three of the mutants compared to the wild type. To investigate the cause of this reduction we have analyzed the efficiency of splicing of the U6 RNA precursor (U6 pre-RNA) in the pre-mRNA splicing mutants. At the restrictive temperature the ratio of unspliced U6 precursor to mature RNA is elevated in the mutants compared to the wild type grown under identical conditions, indicating a defect in U6 pre-RNA splicing. In this regard, the U6 RNA precursor behaves similarly to pre-mRNAs. Unspliced U6 pre-RNA was also detected in wild type cells under certain growth conditions.